Effect of Liver Enzymes, Oxidative Stress and Vitamin D3 in Psoriatic Patients - AL-Fayyadh, Mohanad S. (Iraqi Journal of Science, 2023)
Psoriasis is one of the skin’s chronic inflammatory diseases. Psoriasis etiology isn’t exactly known. Recently, it has been suggested that the imbalances in oxidant-antioxidant status happening because of the increase in reactive oxygen species production (ROS) and/or deficient function regarding the antioxidant system might be included in psoriasis pathogenesis. The major goal is to evaluate the antioxidant defense status in patients experiencing psoriasis and oxidative stresses represented by malondialdehyde (MDA) level and evaluate liver enzymes and vitamin D3. There are some tests of biochemical parameters and vitamins (GSH, MDA, VitD3, SOD, GPx, CAT, AST, ALT, and ALP) are conducted on 35 patients experiencing psoriasis. The results indicated that the significant increase in MDA in psoriatic patients in comparison to the control at (P<0.05), while the level of glutathione (GSH), superoxide dismutase (SOD), glutathione peroxidase (GPX), and catalase (CAT) decreased significantly in psoriatic subjects compare to control. No significances differences in levels of liver enzymes in psoriatic patients compared to the control group.